KAJIAN PERENCANAAN JEMBATAN INTEGRAL - N. Retno Setiati (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Integral bridge is made without existence of movement between spans or between spans with abutment. The road surface is continuously made by the approach embankment. The integral bridge type avoids the problem of maintenance for joins and bearings, in particular if water and dust penetrates through the joints and also effect the bearings, can made safe for road users and simple applicative method. Bridge integral system consist of full integral and semi integral. Integral bridge with spans less than 20 metre to the condition in Indonesia most aptimum use reinforced concrete type with system of full integral, while if more than 20 metre more suggested to user type of prestress with semi integral system. This study explaining about development of integral bridge technology for the type of concrete structure. like calculation method, encumbering paramter and also of desain with simulation model bridge user program analyse structure. For example made integral bridge model for the type of reinforced concrete with single span. Result of study of full integral most is optimum made to spans until 20 m. Keywords : full integral, semi integral, reinforced concrete, maintenance, expansion joint